Analysis of lecturer's experience in the implementation of ICT in teaching economics to undergraduates - Kabora Floria (Journal of Social Studies (JSS), 2016)
This research aims to reveal: (1) the use of ICT by the economics lecturers in the Faculty of Economics, Yogyakarta State University; (2) the reality of their skill in using ICT in teaching; and (3) the impact of ICT use on teaching. This research used the qualitative phenomenology approach. The goal is to describe a “lived experience” of lecturers in the implementation of ICT in teaching Economics to undergraduate students than to explain their experiences. The result reveals three findings. First, the use of ICT in the Faculty of Economics, Yogyakarta State University is that the Internet is used for browsing, LCD projectors for visualizing materials, and Be-Smart (e-learning) for learning support. Second, the lecturers’ skill in using ICT in teaching is in the average level. It is also noticed that the male lecturers are more competent in ICT than female lecturers. Third, the impacts of ICT use on teaching are the increase of the competence and the confidence of the lecturers to transfer knowledge.